Pengembangan Video Animasi Sebagai Media Pembelajaran pada Capaian Sanggul Ukel Tekuk di SMKN 1 Sooko Mojokerto - Avril Lailia Fitri; M.A. Hanny Ferry Fernanda; Mutimmatul Faidah; Biyan Yesi Wilujeng (Program Studi Pendidikan Tata Rias, 2024)
Obstacles that occur during the learning process can impact learning outcomes. Therefore, choosing the right media can facilitate and motivate students in learning. The selection of animation video-based media can boost students' enthusiasm for learning because its varied displays can capture students' attention. The purpose of this study is to investigate the feasibility of animation video-based learning media, how animation video media affects students' learning outcomes, and how students respond to the use of this media. This research uses a quantitative approach, with the research subjects being 31 students from class XI TKKR. Data were collected through observation, learning outcome tests, and questionnaires. The results are as follows: The quality of the feasibility of the animation video-based learning media received an average score of 92%, categorized as